The ebb and flow of adaptive co-management: A longitudinal evaluation of a conservation conflict. Issue 114 (December 2020) - Cox, Thea R.; Butler, James R.A.; Webber, Amanda D.; Young, Juliette C.
Highlights: Long term evaluation of adaptive co-management (ACM) is challenging and rare. ACM in a conservation conflict about seals and salmon was monitored over 11 years. Outcomes were positive, but pre-conditions for ACM to continue were weakening. In response a 'revival' phase was being initiated by local fishery stakeholders. Our participatory method and indicators provide an important feedback loop for ACM. Abstract: Adaptive co-management (ACM) is an emerging approach to the governance of social-ecological systems, but there are few long-term assessments of its efficacy. This is especially true in conservation conflicts, where ACM can mitigate disputes between polarised stakeholders. We evaluated ACM that emerged in 2005 to address conflict between seal conservation and fisheries interests in the Moray Firth, Scotland. We interviewed 20 stakeholders in 2015, repeating a survey carried out in 2011 which applied an indicator framework to measure outcomes and pre-conditions for ACM to continue. In 2015, all but one of the 12 outcome indicators were positive, the exception being the conservation status of salmon. However, pre-conditions for ACM's continuation had weakened, with declines between 2005, 2011 and 2015. These were most marked for three indicators: leaders prepared to champion the process, presence of a bridging organisation or individual, and participation of all impacted stakeholders. The results show that ACM in this conservation conflict is dynamic. Perceived declines in salmon abundance and increases in seal numbers have renewed tensions amongst stakeholders, triggering a 'revival' phase of ACM initiated by fishery interests. Our study provides empirical evidence of ACM's fluid nature, and how resource crises can reignite ACM. We suggest that participatory evaluation is a potentially important early-warning mechanism that can identify remedial action and galvanise stakeholders to respond to the re-emergence of conflict.